New species and new Chinese record of Hypocreaceae from China - Zeng, Zhao-Qing; Wang, Xiang-Hua; Zhuang, Wen-Ying (Phytotaxa, 2024)
Trichoderma clavaticapitatum sp. nov. is described and illustrated based on specimen collected from alpine Hengduan Mountains, Yunnan Province, China. The fungus is characterized by simple, clavate stromata with a capitate fertile part, flask-shaped, subglobose to oblong perithecia, and cylindrical asci containing 16 part-ascospores. Morphological characteristics and analyses of combined RPB2 and TEF1 DNA sequences support its placement in Trichoderma. Differences between the novel species and its close relatives are compared in detail. Additionally, Hypocreopsis rhododendri, a rare fungus, is reported for the first time from the country.